2009
DOI: 10.1111/j.1553-2712.2009.00493.x
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Improving Arrival‐to‐electrocardiogram Time in Emergency Department Chest Pain Patients and the Effect on Door‐to‐balloon Time for ST‐segment Elevation Myocardial Infarction

Abstract: Objectives: The objectives were to determine if an emergency department (ED) could improve the adherence to a door-to-electrocardiogram (ECG) time goal of 10 minutes or less for patients who presented to an ED with chest pain and the effect of this adherence on door-to-balloon (DTB) time for ST-segment elevation myocardial infarction (STEMI) cardiac catheterization (cath) alert patients.Methods: This was a planned 1-month before-and-after interventional study design for implementing a new process for obtaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 32 publications
(22 reference statements)
1
33
0
Order By: Relevance
“…This simple approach minimized the possibility of misdiagnosis or delayed diagnosis of STEMI and shortened the doorto-ECG time. Takakuwa et al (21) employed a similar strategy to reduce the door-to-ECG and D2B time in STEMI patients and found that the door-to-ECG time was indeed reduced significantly; however, the total D2B time without other supplementary measures was not reduced. In our study, use of routine ECG examinations for chest pain patients only resulted in the reduction of the door-to-ECG time from 4 to 2 min.…”
Section: Routine Ecg Examinationmentioning
confidence: 95%
“…This simple approach minimized the possibility of misdiagnosis or delayed diagnosis of STEMI and shortened the doorto-ECG time. Takakuwa et al (21) employed a similar strategy to reduce the door-to-ECG and D2B time in STEMI patients and found that the door-to-ECG time was indeed reduced significantly; however, the total D2B time without other supplementary measures was not reduced. In our study, use of routine ECG examinations for chest pain patients only resulted in the reduction of the door-to-ECG time from 4 to 2 min.…”
Section: Routine Ecg Examinationmentioning
confidence: 95%
“…Care processes associated with shorter door to balloon times are presented in Table 4 and include: ER physician activates cath lab (including several variations) [80,[82][83][84]88,93,95,100], single call to a central page to activate cath lab [78,100], requiring that staff arrive within 20 min of page [100], ER activating cath lab while patient is en route [100], ER and cath lab receiving real time feedback [100], attending cardiologist always on site [100], passive monitoring of physician performance [92], obtaining a pre-hospital ECG (including several variations) [15,16,23,25,29,35,37,57,63,64,77,97], initial culprit vessel PCI before full diagnostic angiography [19,46] and initiation of a quality improvement initiative or critical pathway [17,79,87,[89][90][91]94,96,99]. Longer times are reported with improperly low initial triage of emergency patients with STEMI [66] and use of an intraaortic balloon pump [5].…”
Section: Care Processesmentioning
confidence: 99%
“…This process resulted in delays of about 20 min before diagnosis. Some studies found that increasing the number of ED technicians or triage nursing staff members can reduce door-to-ECG time 25 26. Instead of increasing staff, we altered our process so that nurses and technician staff were trained to know that an ECG should be performed immediately (prior to analysis of vital signs, etc) if a patient arrived with chest pain, and that this was a high priority.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to achieve timely reperfusion for patients with STEMI is dependent on the efficient activation of the cardiac team and execution of PCI, and on the time necessary to transport the patient and prompt contact from a non-PCI capable hospital to a hospital with catheterisation capabilities 25 26. It is recommended that the transfer time should be <60 min 6.…”
Section: Discussionmentioning
confidence: 99%